PERAN BAPENDA DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH MELALUI PAJAK RESTORAN, KOTA TANGERANG SELATAN, BANTEN TAHUN 2023: The Role of BAPENDA in Increasing Local Revenue Through Restaurant Tax in South Tangerang, Banten in 2023 - Diandra Nurul Viani; Reni Dwi Purnomowati (Faculty of Law, Trisakti University, 2025)
Restaurant tax is a crucial component of local taxes that significantly contributes to the fiscal autonomy of regional governments. This study highlights the vital role of the Regional Revenue Agency in enhancing Local Own-Source Revenue through effective restaurant tax collection in South Tangerang City. The main legal issues examined include the extent to which the collection process aligns with South Tangerang Mayor Regulation No. 65 of 2019, and the challenges faced in its implementation. Employing a normative juridical method with descriptive-analytical analysis, the research utilizes both primary and secondary data, analyzed qualitatively. The findings show that in 2023, restaurant tax revenue exceeded the target by 26.34%, indicating compliance with the Mayor Regulation and reflecting its practical effectiveness. However, several obstacles hinder optimal tax collection, including low taxpayer compliance particularly among MSMEs uneven technological infrastructure such as tapping box installations, insufficient qualified personnel in BAPENDA, and weak coordination among government sectors. the regulation is considered a progressive legal instrument and serves as a model for other regions in developing a modern, transparent, and adaptive tax system that supports regional economic resilience and governance.